How preservice teachers use learner knowledge for planning and in-the-moment teaching decisions during guided reading. Issue 2 (3rd April 2019) - Davis, Allison; Griffith, Robin; Bauml, Michelle
ABSTRACT: Decision-making is essential for the work of teaching. Preservice teachers must learn to leverage knowledge about young readers' strengths, needs, and interests in order to plan and teach guided reading lessons skillfully. However, limited research examines preservice teachers' decision-making based on what they know about individual children. In this qualitative case study, we report findings from 12 preservice teachers enrolled in a reading methods course who used teacher knowledge to inform their teaching decisions for guided reading lessons with Kindergarteners. Findings reveal how participants used knowledge of learners to make planning as well as in-the-moment teaching decisions. The data show that most of these decisions were lesson planning decisions about text selection and word solving strategies, indicating that participants were beginning to engage in responsive teaching strategies. This study makes a new contribution to early childhood teacher education literature by underscoring the significance of learner knowledge in the context of authentic teaching practice while learning to teach guided reading to young children.